Spinal cord organoids add an extra dimension to traditional motor neuron cultures - Winanto (2019)
Since Lancaster et al. (2013) first described the formation of self-organizing cerebral organoids for modeling neurodevelopmental disorders, it became evident that three-dimensional (3D) neural organoid cultures are more superior systems for modeling neurodevelopment and neurodegeneration in human. The use of a spinning bioreactor to grow organoids allows better nutrient absorption and enhances formation of neuroepithelial-like zones, making it a great tool to study neurodevelopment and neurodegeneration. Neural organoids are 3D cell culture systems formed by proliferating, differentiating, migrating and self-organizing pools of neural progenitors. They mimic brain structures in their cell type composition, cytoarchitecture, and to some extent maturity and functionality (Lancaster et al., 2013).